Human Rights Violations during Armed Conflict in Nepal - Khanal, Prem Raj (KMC Research Journal, 2017)
The armed conflict of Nepal was a conflict between government forces and Maoist rebels which started from 13 February 1996 and lasted 21 November 2006. The Communist Party of Nepal (Maoist) had begun the war with the aim of overthrowing the Nepalese monarchy and establishing the “People’s Republic of Nepal.” A decade-long armed conflict was formally ended with signing of the “Comprehensive Peace Accord (CPA)” between government of Nepal and Communist Party of Nepal (Maoists) on 21 November 2006. This article does not describe the political, economic and other dimension of the armed conflict in Nepal. However, it tells about the different aspects of the human rights violations by State and Maoists in a decade-long (from 1996 to 2006) war in Nepal.